2011
DOI: 10.1002/aic.12273
|View full text |Cite
|
Sign up to set email alerts
|

Granular activated carbon adsorption process for removing trichloroethylene from groundwater

Abstract: Batch adsorption capacity experiments and continuous flow breakthrough experiments were conducted to compare the effectiveness of seven granular activated carbons (GACs) in removing trichloroethylene (TCE) from groundwater. The order of GACs' adsorptive capacities for TCE was the same as their phenol numbers (indicator for \1 nm micropores). A small amount of methanol (0.05% v/v) did not affect the pure water TCE capacities, which were notably reduced by the small organic constituents of tap water. The breakth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…An organic pollutant is most strongly adsorbed on the internal surface area of pores slightly larger than its effective MD; GAC's relative capacity for MTBE (MD 5 0.6 nm) was in the same order as its phenol number [13] which is also a good capacity indicator for such small organic molecules as nitrobenzene [14], chloroform [24], and trichloroethylene [25]. An organic pollutant is most strongly adsorbed on the internal surface area of pores slightly larger than its effective MD; GAC's relative capacity for MTBE (MD 5 0.6 nm) was in the same order as its phenol number [13] which is also a good capacity indicator for such small organic molecules as nitrobenzene [14], chloroform [24], and trichloroethylene [25].…”
Section: Mtbe Removal Effectiveness Of Four Gacsmentioning
confidence: 99%
“…An organic pollutant is most strongly adsorbed on the internal surface area of pores slightly larger than its effective MD; GAC's relative capacity for MTBE (MD 5 0.6 nm) was in the same order as its phenol number [13] which is also a good capacity indicator for such small organic molecules as nitrobenzene [14], chloroform [24], and trichloroethylene [25]. An organic pollutant is most strongly adsorbed on the internal surface area of pores slightly larger than its effective MD; GAC's relative capacity for MTBE (MD 5 0.6 nm) was in the same order as its phenol number [13] which is also a good capacity indicator for such small organic molecules as nitrobenzene [14], chloroform [24], and trichloroethylene [25].…”
Section: Mtbe Removal Effectiveness Of Four Gacsmentioning
confidence: 99%
“…According to its various appearance, AC is divided into cylindrical activated carbon (CAC) (Wang, J. C., et al, 2008), granular activated carbon (GAC) (Huang, L., et al, 2011, Saoudi&Hamdaoui, 2011, powder activated carbon (PAC) (Li, et al, 2009a, Li, et al, 2009b, Li, et al, 2010b and acivated carbon fiber (ACF) (Li, et al, 2010a). In terms of extent of its pore development, AC is classified as microporous activated carbon/activated carbon fiber (Li, et al, 2009a, Li, et al, 2010a and mesoporous activated carbon (Zhang, Y., et al, 2011b).…”
Section: Simple Aromatic Compoundsmentioning
confidence: 99%
“…Thus, sorption was the one of the major mechanisms, which caused the decrease in TCE concentrations in solution containing porous materials (Mudliar et al 2010;Wei et al 2010). Huang et al (2010) used different types of PAC to evaluate the adsorption mechanisms using porous materials. Their results indicated that the adsorption of natural organic matter (NOM) in water by porous materials would cause the occurrence of competitive adsorption mechanism, which resulted in the decease in TCE removal.…”
Section: Membrane Resistance Analysismentioning
confidence: 99%
“…Thus, alternative pre-treatment technology for groundwater purification is required. Fiber ball filtration (FF) has been applied to replace traditional sand filtration and biofiltration for small particle removal in recent years (Huang et al 2010). Xue et al (2008) used FF as the pre-treatment unit for hotel wastewater treatment before the dual membrane system (UF/RO) was applied for water reclamation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation